Impact of the mode of protraction of basal insulin therapies on their pharmacokinetic and pharmacodynamic properties and resulting clinical outcomes. Issue 1 (26th September 2016) - Heise, Tim; Mathieu, Chantal
Abstract : Manufacturers of insulin products for diabetes therapy have long sought ways to modify the absorption rate of exogenously administered insulins in an effort to better reproduce the naturally occurring pharmacokinetics of endogenous insulin secretion. Several mechanisms of protraction have been used in pursuit of a basal insulin, for which a low injection frequency would provide tolerable and reproducible glucose control; these mechanisms have met with varying degrees of success. Before the advent of recombinant DNA technology, development focused on modifications to the formulation that increased insulin self‐association, such as supplementation with zinc or the development of preformed precipitates using protamine. Indeed, NPH insulin remains widely used today despite a frequent need for a twice‐daily dosing and a relatively high incidence of hypoglycaemia. The early insulin analogues used post‐injection precipitation (insulin glargine U100) or dimerization and albumin binding (insulin detemir) as methods of increasing therapeutic duration. These products approached a 24‐hour glucose‐lowering effect with decreased variability in insulin action. Newer basal insulin analogues have used up‐concentration in addition to precipitation (insulin glargine U300), and multihexamer formation in addition to albumin binding (insulin degludec), to further increase duration of action and/or decrease the day‐to‐day variability of the glucose‐lowering profile. Clinically, the major advantage of these recent analogues has been a reduction in hypoglycaemia with similar glycated haemoglobin control when compared with earlier products. Future therapies may bring clinical benefits through hepato‐preferential insulin receptor binding or very long durations of action, perhaps enabling once‐weekly administration and the potential for further clinical benefits.